Second messenger control of chromatin remodeling - Rando, Oliver J.; Chi, Tian H.; Crabtree, Gerald R. (Nature Structural Biology, 2003)
Two recent studies show that some ATP-dependent chromatin remodeling complexes are subject to control by a surprising set of regulators — phosphoinositols. These studies extend earlier observations in mammalian cells and suggest that second messengers are regulators of chromatin remodeling.